2012
DOI: 10.2535/ofaj.88.141
|View full text |Cite
|
Sign up to set email alerts
|

Cell- and region-specific expression of sugar chains in the mouse epididymal epithelium using lectin histochemistry combined with immunohistochemistry

Abstract: -I B lectin), respectively. These findings indicate that the selectivity in lectin reactivity for distinct cell types and segment-dependent staining in the epididymis may be related to cellular and regional differences in function. Furthermore, because some lectins stain particular cells or cellular compartments selectively, these lectins could be useful markers for histopathological evaluation of diseases or diagnosis of male infertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“…Lectin histochemistry and control staining were performed as described in our previous paper (Tajiri et al, 2012). The 6 biotinylated lectins and their inhibitory sugars used in this study are shown in Table 1.…”
Section: Lectin Histochemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…Lectin histochemistry and control staining were performed as described in our previous paper (Tajiri et al, 2012). The 6 biotinylated lectins and their inhibitory sugars used in this study are shown in Table 1.…”
Section: Lectin Histochemistrymentioning
confidence: 99%
“…The method for double fluorescent staining was identical to the one described in our previous paper (Tajiri et al, 2012).…”
Section: Double Fluorescent Staining Using Lectin Histochemistry and mentioning
confidence: 99%
See 1 more Smart Citation
“…Their full names (natural sources), abbreviations, carbohydrate specificities, and binding inhibitors are listed in Table 1. Lectin histochemical staining was performed as previously described [26,30]. Briefly, deparaffinized sections were incubated in citrate buffer solution (pH 6.0), and their antigenicities were enhanced in an autoclave (121°C, 1 min).…”
Section: Lectin Histochemistrymentioning
confidence: 99%
“…Lectin histochemical staining was performed as described in our previous paper 20) . Briefly, deparaffinized sections were incubated with citrate buffer solution (pH 6.0), and their antigenicities were enhanced in an autoclave (121°C, 1 min).…”
Section: Lectin Histochemistrymentioning
confidence: 99%